THE INFLUENCE OF FINANCIAL TARGET, INEFFECTIVE MONITORING, RATIONALIZATION AND DUALISM POSITION ON THE FRAUDULENT FINANCIAL STATEMENT WITH A AUDIT COMMITTEE AS A MODERATION ISLAMIC COMMERCIAL BANKS IN INDONESIA PERIOD 2015 – 2021 - Sahri, Sahid Alfi; Bawono, Anton (UIN Mataram, 2023)
Abstract This study has the intention to find out how the influence of financial target, ineffective monitoring, rationalization and dualism position on fraudulent financial statement with audit committees as a moderating variable in islamic commercial bank in Indonesia. In the research that has been carried out, the method used is quantitative by processing panel data obtained from the annual report for each islamic commercial bank. After conducting the test, the result obtained that the financial target variable has positive but not significant (no effect) on fraudulent financial statement. Ineffective monitoring has a negative but not significant (no effect) on fraudulent financial statement. Rationalization has a negative and significant effect on fraudulent financial statement. Dualism position has a negative and significant effect on fraudulent financial statement. The audit committee has a negative and not significant (no effect) on fraudulent financial statement. The audit committe was unable to moderate the effect of financial target on fraudulent financial statement. The audit committee was unable to moderate the effect of ineffective monitoring on fraudulent financial statement. The audit committee is able to moderate the effect of rationalization on fraudulent financial statement. The audit committee is able to moderate the effect of dualism position on fraudulent financial statement fraud. In conclusion, financial target, ineffective monitoring, rationalization dan dualism position have no effect on fraudulent financial statement. The audit committe was unable to moderate financial target dan ineffective monitoring and other variable cannot be moderated by committee audit.